LEGAL VOID IN THE CUSTOMS LAW REGARDING LAWSUITS: A COMPARATIVE ANALYSIS WITH THE TAX LAW: KEKOSONGAN HUKUM UPAYA GUGATAN DALAM UNDANG-UNDANG KEPABEANAN: ANALISIS PERBANDINGAN DENGAN UNDANG-UNDANG PERPAJAKAN - Doni Budiono (Asosiasi Dosen Hukum Acara Perdata (ADHAPER), 2026)
Law No. 10 of 1995 on Customs, as amended by Law No. 17 of 2006, does not recognize a lawsuit remedy as a legal avenue. Instead, it provides objection, correction of assessment, reduction or cancellation of administrative sanctions, judicial review, and appeal to the Tax Court. This differs from Law No. 6 of 1983 on General Provisions and Tax Procedures, last amended by Law No. 6 of 2023 on Job Creation, which expressly provides a lawsuit remedy in addition to appeal. This regulatory difference creates a legal vacuum in the customs dispute settlement system, because many administrative decisions issued by customs authorities are more appropriately challenged through a lawsuit than through an appeal. In practice, customs disputes frequently end with inadmissibility rulings when the disputed decision is considered not to qualify as an object of lawsuit. Furthermore, the customs appeal requirement that obliges full payment of import duty, export duty, and import related taxes before an application is filed imposes an additional burden on justice seekers, especially when the dispute concerns procedural issues only. This condition produces uncertainty in legal protection for importers, exporters, and customs service users who face administrative decisions beyond tariff classification and customs valuation. This study analyzes the legal vacuum concerning lawsuit remedies in the customs system by comparing it with the tax law framework. It uses normative legal research with statutory, conceptual, and comparative approaches. The findings are expected to contribute to the development of customs law and to encourage reform of the Customs Law to achieve harmonization with tax law and to ensure adequate legal protection for affected parties.